2019
DOI: 10.1155/2019/6029403
|View full text |Cite
|
Sign up to set email alerts
|

Drug Induced Liver Injury Attributed to a Curcumin Supplement

Abstract: More severe reactions, higher acute liver failure rates, and higher recurrence rates on re-challenge occur with supplement-related Drug Induced Liver Injury (DILI) (Medina-Caliz et al., 2018). We report a case of curcumin-induced hepatocellular DILI in a 78-year old female admitted with jaundice, with a one-month latency. Extensive evaluation for alternative etiologies of hepatotoxicity was unremarkable. The Roussel Uclaf Causality Assessment Method (RUCAM) score of 6 for the supplement indicated a probable as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The safety of orally administered curcumin has been clearly demonstrated: the US Food and Drug Administration has approved curcumin as a compound "generally recognized as safe" and also JECFA (The Joint FAO/WHO Expert Committee on Food Additives) and EFSA (European Food Safety Authority) reported the ADI (acceptable daily intake) value of 0-3 mg•kg −1 for curcumin [40]. However, it has to been taken into account that very few reports on the potential adverse effects of curcumin exist: recently, a case report showed a liver injury attributed to a curcumin supplement in a woman with jaundice [41]. Curcumin could also interfere with systemic iron metabolism, suggesting limited application of this compound in patients with chronic disease or anemia [42].…”
Section: Curcumin: Metabolism and Bioavailabilitymentioning
confidence: 99%
“…The safety of orally administered curcumin has been clearly demonstrated: the US Food and Drug Administration has approved curcumin as a compound "generally recognized as safe" and also JECFA (The Joint FAO/WHO Expert Committee on Food Additives) and EFSA (European Food Safety Authority) reported the ADI (acceptable daily intake) value of 0-3 mg•kg −1 for curcumin [40]. However, it has to been taken into account that very few reports on the potential adverse effects of curcumin exist: recently, a case report showed a liver injury attributed to a curcumin supplement in a woman with jaundice [41]. Curcumin could also interfere with systemic iron metabolism, suggesting limited application of this compound in patients with chronic disease or anemia [42].…”
Section: Curcumin: Metabolism and Bioavailabilitymentioning
confidence: 99%
“…With 11,609 the largest HILI case number was published in 2019 ( Figure 3 ) as a consequence of the ongoing worldwide use of RUCAM for assessing causality in suspected HILI cases ( Table 4 ). In particular, contributing countries were in alphabetical order Australia [ 29 ], Brazil [ 183 ], China [ 48 , 196 , 197 , 198 , 199 , 200 , 201 ], Germany [ 213 , 214 , 215 ], India [ 217 ], Italy [ 222 ], Korea [ 103 ], Spain [ 115 , 117 , 240 , 241 , 242 ], Switzerland [ 244 ], and the US [ 245 , 246 , 247 , 248 , 249 , 250 , 251 , 252 , 253 , 254 ]. Most of the 11,619 HILI cases published in 2019 were from China [ 48 , 196 ] and Korea [ 103 ], with 6971 cases published by Shen et al [ 48 ], 2019 cases reported by Byeon et al [ 103 ], and 1552 cases provided by Chow et al [ 196 ].…”
Section: Worldwide Publications Of Hili Cases Assessed For Causalimentioning
confidence: 99%
“…Additionally, the recurrence of liver malfunction was more likely after a second re-exposure. Incidentally, Iman et al described a case of curcumin-induced hepatocellular damage in a 78 year old woman admitted with jaundice, with a latency time of one month [78]. Laboratory investigations failed to find any other cause of acute hepatitis.…”
Section: Side Effects Of Curcuminmentioning
confidence: 99%